2016
DOI: 10.1111/ibi.12444
|View full text |Cite
|
Sign up to set email alerts
|

Density‐dependent effects on reproductive performance in a recovering population of White‐tailed Eagles Haliaeetus albicilla

Abstract: Understanding the mechanisms that shape density‐dependent processes and population dynamics is often essential for species conservation. Two key mechanisms of density‐dependent reductions in reproductive performance are a limited access to foraging habitats (the habitat heterogeneity hypothesis) and territorial aggression towards conspecifics (the interference competition hypothesis) at high population densities. Disentangling the relative importance of these mechanisms within populations below their carrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
(133 reference statements)
2
16
0
Order By: Relevance
“…Studies on similar systems have mainly reported regulation through IAH (Fern andez et al 1998, Oppel et al 2015, Fern andez-Bellon et al 2016) with a few studies on colonial species supporting the HHH (Kokko et al 2004). In agreement with Heuck et al (2017), our results suggest that the habitat heterogeneity and interference competition hypotheses are not necessarily mutually exclusive, as mechanisms of density-dependent population regulation can determine the reproductive performance of a raptor population simultaneously. The rainy climate of Bizkaia imposed conditions that allowed the HHH to act, whereas in less rainy climates its importance may decrease, leading to the IAH being more important.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Studies on similar systems have mainly reported regulation through IAH (Fern andez et al 1998, Oppel et al 2015, Fern andez-Bellon et al 2016) with a few studies on colonial species supporting the HHH (Kokko et al 2004). In agreement with Heuck et al (2017), our results suggest that the habitat heterogeneity and interference competition hypotheses are not necessarily mutually exclusive, as mechanisms of density-dependent population regulation can determine the reproductive performance of a raptor population simultaneously. The rainy climate of Bizkaia imposed conditions that allowed the HHH to act, whereas in less rainy climates its importance may decrease, leading to the IAH being more important.…”
Section: Discussionsupporting
confidence: 87%
“…This effect should be considered when modelling future predictions of population trends of Griffon Vultures and implementing actions related to the management of this species. In agreement with Heuck et al (2017), our results suggest that the habitat heterogeneity and interference competition hypotheses are not necessarily mutually exclusive, as mechanisms of density-dependent population regulation can determine the reproductive performance of a raptor population simultaneously. It would be interesting to conduct similar analyses in populations under different weather conditions to elucidate the importance of environmental variability on IAH and HHH interactions.…”
Section: Discussionsupporting
confidence: 87%
“…We included nearest neighbour distance (NND, in meters, log transformed) as the distances to the closest present neighbour per year (see e.g. [61,62] for recent literature on density dependence in other raptor populations). We chose NND because studies exploring different measurements found the distance to nearest neighbours to be the best predictor for density dependence (e.g.…”
Section: Plos Onementioning
confidence: 99%
“…Positive group-size effects on productivity are so large in many cooperatively breeding birds they can offset negative effects of competition on productivity (Courchamp et al 1999, Meade et al 2010, even in low quality habitat (Cusick et al 2018). This could have important implications for conservation of cooperative breeders with narrow habitat requirements because future declines in productivity may reflect density-dependent competition and small group sizes, rather than habitat degradation (Heuck et al 2017). Therefore, in addition to long-term data on territory quality, identifying factors moderating effects of density on group size and productivity trends for cooperative breeders requires long-term data at the scale of individual territories where groups interact and compete (Brouwer et al 2006).…”
mentioning
confidence: 99%